Effect of evacuation on liver function after the Fukushima Daiichi Nuclear Power Plant accident: The Fukushima Health Management Survey - Takahashi, Atsushi (J Epidemiol, 2017)
BACKGROUND: The Great East Japan Earthquake and subsequent Fukushima Daiichi Nuclear Power Plant accident caused residents to switch from their normal lives to lives focused on evacuation. We evaluated liver function before and after this disaster to elucidate the effects of evacuation on liver function. METHODS: This study was a longitudinal survey of 26,006 Japanese men and women living near the Fukushima Daiichi Nuclear Power Plant. This study was undertaken using data from annual health checkups conducted for persons aged 40–90 years between 2008 and 2010. Follow-up examinations were conducted from June 2011 to the end of March 2013, with a mean follow up of 1.6 years. Changes in liver function before and after the disaster were compared among evacuees and non-evacuees. We also assessed groups according to alcohol drinking status. RESULTS: The prevalence of liver dysfunction significantly increased in all participants from 16.4% before to 19.2% after the disaster. The incidence of liver dysfunction was significantly higher in evacuees than in non-evacuees. Multivariate logistic regression analysis showed that evacuation was significantly associated with liver dysfunction among residents. CONCLUSIONS: This is the first study to show that evacuation due to the Fukushima Daiichi nuclear power plant disaster was associated with an increase in liver dysfunction.